Матричный бесконечномерный аналог теоремы Винера о локальном обращении преобразований Фурье - Шуренков, В.М.; Дегтярь, С.В. (Український математичний журнал, 1995)
A matrix infinite-dimensional analog of the Wiener theorem on local inversion of Fourier transforms is proved.